2019
DOI: 10.1002/mma.5786
|View full text |Cite
|
Sign up to set email alerts
|

How vector feeding preference through an infectious host relates to the seasonal transmission rates in a mathematical vector‐host model

Abstract: Vector-borne diseases, such as leishmaniasis, dengue, malaria, and yellow fever, transmitted by microparasites show periodic fluctuations in their prevalence.The novelty of this research is to assess the relationship between the vector feeding preference for an infectious host and the annual seasonal transmission through a vector-host mathematical model. For the first time, numerical simulations illustrate that by increasing the vector feeding preference value in the transmission dynamics, periodic fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For example, vector density and longevity would also increase the transmission rate of these pathogens [ 361 ]. Studies have even identified the feeding preferences of vectors and their connection to disease transmission [ 362 , 363 ]. Another study found an effect between habitat fragmentation and the infection rate of vectors with Plasmodium sp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, vector density and longevity would also increase the transmission rate of these pathogens [ 361 ]. Studies have even identified the feeding preferences of vectors and their connection to disease transmission [ 362 , 363 ]. Another study found an effect between habitat fragmentation and the infection rate of vectors with Plasmodium sp.…”
Section: Discussionmentioning
confidence: 99%